Method for industrially producing super-hydrophobic iron phosphide / cobalt nickel phosphide electro-catalytic material

The method of growing nanorod-like iron phosphide/cobalt nickel phosphide structures on nickel foam addresses the inefficiencies of current catalysts by enhancing gas-liquid exchange and electron transfer, enabling efficient and scalable water electrolysis.

CN119243231APending Publication Date: 2025-01-03LONGMEN LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411326489.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Current methods for producing hydrogen through water electrolysis require scarce and expensive platinum-based catalysts for hydrogen evolution and precious metal-based catalysts for oxygen evolution, necessitating separate catalysts for each reaction, which are inefficient and complex, and lack scalable industrial production methods.

Method used

A method for producing super-gas-repellent iron phosphide/cobalt nickel phosphide electrocatalytic materials by in-situ growing nanorod-like structures on nickel foam using a simple process, enhancing hydrophilic and gas-repellent properties to accelerate gas-liquid exchange.

Benefits of technology

The nanorod-like structure provides a larger surface area for efficient gas-liquid exchange, rapid electron transfer, and stable bifunctional water electrolysis performance, suitable for both anode and cathode applications, with reduced energy consumption and potential for large-scale industrial use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243231A_ABST
    Figure CN119243231A_ABST
Patent Text Reader

Abstract

The invention provides a method for industrially producing a super-hydrophobic iron phosphide / cobalt nickel phosphide electro-catalytic material, which comprises the following steps: cleaning foamed nickel, adding a cobalt source, an iron source, ammonium fluoride and urea into deionized water according to a molar ratio of (3-5): 1: 6: 30, stirring to obtain a solution A, putting the cleaned foamed nickel into the solution A, and carrying out water bath at the water bath temperature of 60-90 DEG C for several hours, so as to obtain the super-hydrophobic iron phosphide / cobalt nickel phosphide electro-catalytic material. And after the reaction is finished, cooling to room temperature, taking out the foamed nickel, washing with deionized water and ethanol for multiple times to obtain the foamed nickel with a ferric hydroxide / cobalt hydroxide nickel precursor, and then carrying out heat treatment on the vacuum-dried foamed nickel with the ferric hydroxide / cobalt hydroxide nickel precursor to obtain the nickel-based composite material. And then preparing the bifunctional heterostructure iron phosphide / cobalt nickel phosphide electro-catalytic material by using a CVD phosphorus source deposition method. The iron phosphide / cobalt nickel phosphide electro-catalytic material which can be used as HER and OER reaction catalysts at the same time is obtained through the method, and the iron phosphide / cobalt nickel phosphide electro-catalytic material has the advantages of being simple in process, suitable for industrial production, good in stability, super in hydrophobic property and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrocatalytic materials, in particular to a method for industrially producing super-gas-repellent iron phosphide / cobalt nickel phosphide electrocatalytic materials. Background Art

[0002] Energy crisis and environmental problems force people to look for clean and renewable alternative energy sources. Hydrogen has the advantages of high energy density, high energy conversion efficiency, and no pollution from combustion products, making it an ideal alternative energy source. Compared with traditional hydrogen production methods, water electrolysis is a simple, efficient, and environmentally friendly way to produce hydrogen. It uses electricity to decompose water into hydrogen and oxygen, and the products are easy to separate. At present, the methods for preparing hydrogen by water electrolysis include hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Platinum (Pt)-based electrocatalysts are the benchmark catalysts for hydrogen evolution reaction, but they are limited by their scarcity and high price. Precious metal Ir / Ru-based materials are the benchmark catalysts for oxygen evolution reaction, but the overpotential of OER catalyst IrO2 is about 300-400mV, which still does not reach the activity of ideal OER catalysts. In addition, current research mainly focuses on the development of monofunctional catalysts for HER or OER, which means that two different types of catalysts need to be designed to achieve practical applications, increasing the complexity of electrolysis equipment. Therefore, we need to explore abundant transition metal-based bifunctional catalysts with excellent electrocatalytic performance and superior economic benefits to achieve overall water splitting with high performance to produce H2 and O2.

[0003] Most of the catalysts prepared in current research are powders, which need to be attached to the cathode and anode through a binder, which not only reduces their conductivity, but also easily falls off during the catalytic process. The self-supporting electrode has strong mechanical strength and controllable morphology because the catalyst grows in situ on its surface. Common methods for preparing self-supporting catalysts include hydrothermal method, electrodeposition method, etc. These methods require large energy consumption and usually need to react in a closed environment. There is still a long way to go to achieve the goal of large-scale industrial production, so it is urgent to find a method with low energy consumption, simple process and controllable reaction. The purpose of the present invention is to synthesize and prepare a catalyst suitable for industrial production by designing simple process conditions, and to improve the hydrophilic and gas-repellent properties of the catalyst by changing the morphology of the catalyst, so as to accelerate the gas-liquid exchange in the reaction process. Summary of the invention

[0004] In order to address the deficiencies in the prior art, the present invention provides a method for industrially producing super-gas-repellent iron phosphide / cobalt nickel phosphide electrocatalytic materials. The present invention synthesizes and prepares a catalyst suitable for industrial production by designing simple process conditions, and improves the hydrophilic and gas-repellent properties of the catalyst by changing the structural characteristics of the catalyst, thereby accelerating the gas-liquid exchange during the reaction.

[0005] In order to achieve the above object, the specific scheme adopted by the present invention is: A method for industrially producing super-gas-repellent iron phosphide / cobalt nickel phosphide electrocatalytic material, using nickel foam as a substrate, and in-situ growing array-arranged iron phosphide / cobalt nickel phosphide in a nanorod-like structure on its surface; The industrial production method of iron phosphide / cobalt nickel phosphide electrocatalytic material mainly includes the following steps: Step 1: Clean the nickel foam Step 2: Preparation of ferric hydroxide / cobalt nickel hydroxide precursor A cobalt source, an iron source, ammonium fluoride and urea are added to deionized water in a molar ratio of (3-5):1:6:30, and stirred to obtain a solution A. The nickel foam cleaned in step 1 is placed in the solution A, and is bathed in a water bath at a temperature of 60-90° C. for several hours. After the reaction is completed, the nickel foam is cooled to room temperature, and the nickel foam is taken out, and is rinsed with deionized water and ethanol for several times, and finally vacuum dried to obtain a nickel foam with an iron hydroxide / cobalt hydroxide nickel precursor; Step 3: Heat treatment of nickel foam with ferric hydroxide / cobalt hydroxide nickel precursor The nickel foam with the iron hydroxide / cobalt hydroxide nickel precursor obtained in step 2 is placed in a tube furnace, and is heated to 350-450° C. at a heating rate of 2-5° C. / min under the protection of an inert atmosphere for heat treatment, and is kept warm for 1-5 hours, and is taken out after cooling to obtain a heat-treated product; the toughness of the iron hydroxide / cobalt hydroxide nickel precursor can be improved by heat treatment; Step 4: Preparation of bifunctional heterostructured iron phosphide / cobalt nickel phosphide electrocatalytic material A phosphorus source is placed in the upwind section of the tubular furnace, and the heat-treated product obtained in step 3 is placed 1-5 cm away from the phosphorus source. The product is heated to 350-450°C at a heating rate of 2-5°C / min in an inert atmosphere for CVD phosphorus source deposition. The product is kept warm for 1-5 hours, and is taken out after cooling. Thus, an array of nanorod-like iron phosphide / cobalt phosphide nickel is in situ grown on the surface of the nickel foam. The molar ratio of the phosphorus source to the active substance in situ grown on the heat-treated product (referring to the iron hydroxide / cobalt hydroxide nickel precursor after heat treatment) is (5-2):1.

[0006] Furthermore, in step 1, the nickel foam is ultrasonically treated in a 2-3 mol hydrochloric acid solution, an acetone solution and a deionized water solution for several minutes in sequence to remove impurities in the nickel foam, and then dried in a low-temperature vacuum environment.

[0007] Furthermore, the cobalt source is at least one of cobalt nitrate and cobalt chloride; the iron source is at least one of ferric nitrate and ferric chloride.

[0008] Furthermore, in step 2, the vacuum drying temperature is 60-90°C.

[0009] Furthermore, in step three or step four, the inert atmosphere is any one of argon, nitrogen, and a hydrogen-argon mixture.

[0010] Furthermore, the phosphorus source is any one of sodium hypophosphite and red phosphorus.

[0011] Beneficial effects: (1) The electrocatalytic material of the present invention will first form numerous fine grains on the surface of the nickel foam / nickel mesh during the water bath reaction. Since the energy of the temperature field is relatively low, the fine grains have insufficient energy and will not combine with each other to form coarse grains. Therefore, they will continue to grow in a direction perpendicular to the surface, thereby obtaining a rod-like structure.

[0012] (2) The present invention can prepare iron hydroxide / cobalt hydroxide nickel precursor under low temperature and normal pressure hydrothermal conditions, which is suitable for industrial production.

[0013] (3) The nanorod-like structure provides a larger specific surface area, which is conducive to gas-liquid exchange and accelerates the reaction.

[0014] (4) The heterostructure is conducive to the rapid transfer of electrons and provides an electron cloud density around the active site that is more favorable for HER / OER reactions.

[0015] In summary, the present invention successfully prepared a nanorod-shaped self-supporting catalyst with a controllable nanorod-shaped morphology through the preparation method of water bath, heat treatment and CVD deposition process. The obtained electrode material has excellent hydrophilic and air-repellent properties, exhibits rapid gas-liquid exchange ability and excellent bifunctional water electrolysis performance, can be used in the anode and cathode of the electrolytic cell at the same time, and is a potential electrocatalytic complete water splitting catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the SEM image of the catalytic material prepared in Example 1.

[0017] Figure 2 This is the XRD pattern of the catalytic material prepared in Example 1.

[0018] Figure 3 This is the TEM image of the catalytic material prepared in Example 1.

[0019] Figure 4 This is the polarization curve of the catalytic material prepared in Example 1 as an OER catalyst.

[0020] Figure 5 This is the polarization curve of the catalytic material prepared in Example 1 as a HER catalyst.

[0021] Figure 6 The catalytic material prepared in Example 1 has a -2Stability curves at different current densities.

[0022] Figure 7 The catalytic material prepared in Example 1 is -10 mA cm -2 Stability curves at different current densities.

[0023] Figure 8 This is a diagram of bubble precipitation of the catalytic material prepared in Example 1 during the OER constant current test.

[0024] Fig. 9 This is a diagram of bubble precipitation during the HER constant current test of the catalytic material prepared in Example 1.

[0025] Fig.10 This is a SEM image of the catalytic material prepared in Example 1 after OER reaction.

[0026] Fig.11 This is the SEM image of the catalytic material prepared in Example 2.

[0027] Fig.12 This is the polarization curve of the catalytic material prepared in Example 2 as an OER catalyst.

[0028] Fig.13 This is the polarization curve of the catalytic material prepared in Example 2 as a HER catalyst.

[0029] Fig.14 This is the SEM image of the catalytic material prepared in Comparative Example 1.

[0030] Fig.15 This is the polarization curve of the catalytic material prepared in Comparative Example 1 as an OER catalyst.

[0031] Fig.16 This is the polarization curve of the catalytic material prepared in Comparative Example 1 as a HER catalyst.

[0032] Fig.17 This is the SEM image of the catalytic material prepared in Comparative Example 2.

[0033] Fig.18 This is the polarization curve of the catalytic material prepared in Comparative Example 2 as an OER catalyst.

[0034] Fig.19 This is the polarization curve of the catalytic material prepared in Comparative Example 2 as a HER catalyst.

[0035] Fig. 20 This is the polarization curve of the catalytic material prepared in Comparative Example 3 as a HER catalyst.

[0036] Fig.21This is the polarization curve of the catalytic material prepared in Comparative Example 3 as a HER catalyst.

[0037] Fig. 22 This is the polarization curve of the catalytic material prepared in Comparative Example 3 as a HER catalyst.

[0038] Fig.23 This is the polarization curve of the catalytic material prepared in Comparative Example 4 as a HER catalyst.

[0039] Fig.24 This is the polarization curve of the catalytic material prepared in Comparative Example 4 as an OER catalyst.

[0040] Fig.25 This is the polarization curve of the catalytic material prepared in Comparative Example 4 as a HER catalyst. DETAILED DESCRIPTION

[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0042] The purpose of the present invention is to improve the characteristics of the electronic structure of single metal phosphide that is not conducive to electrocatalytic reaction, utilize the electronic synergistic effect between bimetallic or polymetallic, guide the directional transfer of electrons between heterostructures, improve the electronic structure near the active site, and design and construct a gas-repellent structure to improve the gas-repellent property, so as to achieve efficient and complete water splitting. In the present invention, the iron phosphide / cobalt nickel phosphide heterostructure is formed between Fe, Co, Ni and P elements, which can work in an environment with a large current density and has the potential for large-scale industrial application.

[0043] Example 1 A method for preparing a bifunctional heterostructured iron phosphide / cobalt nickel phosphide electrocatalytic material mainly comprises the following steps: 1) The nickel foam was ultrasonically treated in 2 mol hydrochloric acid solution, acetone solution and deionized water solution for 15 minutes to remove impurities in the nickel foam, and then dried in a vacuum environment at 60 °C for 10 h; 2) Dissolve the cobalt source, iron source, ammonium fluoride and urea in a molar ratio of 3:1:6:30 and keep the total mass of the metal salt at 2 mol in 50 L aqueous solution, stir for 30 minutes to obtain solution A, put the nickel foam treated in step 1) into solution A, and place it in a water bath at 90 ° C for 7 hours, take out the nickel foam after cooling to room temperature, rinse it with deionized water and ethanol several times, and finally dry it in a vacuum environment at 60 ° C for 10 hours to obtain a nickel foam with iron hydroxide / cobalt hydroxide nickel precursor; 3) Heat-treating the nickel foam with the iron hydroxide / cobalt hydroxide nickel precursor obtained in step (2) at a heating rate of 5°C / min to 350°C under an inert atmosphere, keeping the temperature for 2h, and taking out after cooling; 4) Deposit a phosphorus source by CVD method, wherein sodium hypophosphite is selected as the phosphorus source, and the phosphorus source is placed in the upwind section of the tubular furnace. The heat-treated product obtained in step 3 is placed 2 cm away from the phosphorus source, and heated to 350 °C at a heating rate of 2 °C / min in a nitrogen atmosphere, and kept warm for 2 h. After cooling, the product is taken out to obtain an iron phosphide / cobalt nickel phosphide electrocatalytic material, named FeP / CoNiP / NF.

[0044] The product obtained in Example 1 is analyzed as follows.

[0045] The SEM test was performed using a FEI Quanta FEG250 high-resolution field emission scanning electron microscope. The product obtained in Example 1 was cut into target size, adhered to a black conductive adhesive, and then subjected to gold spraying to prepare for SEM testing. The SEM image of the product obtained in Example 1 is shown in FIG. Figure 1 As shown, the uniformly grown nanorod-like morphology of uniform size on the surface of nickel foam further demonstrates the feasibility of synthesizing FeP / CoNiP / NF using the method of the present invention. The nanorod-like morphology is conducive to the rapid escape of bubbles, avoids "poisoning" of active sites, and is conducive to rapid gas-liquid exchange.

[0046] The XRD test uses a Bruker D8 advance X-ray diffractometer to analyze the phase composition and crystal structure of the material surface. The XRD pattern of the product obtained in Example 1 is as follows: Figure 2 As shown, the main components of the nickel foam surface are CoNiP and FeP phases.

[0047] The morphology and phase distribution of the materials were further analyzed using a JEOL-JEM 2100 F-type transmission electron microscope. Figure 3 It shows that the size of the nanorods in the product obtained in Example 1 is approximately 60 nm.

[0048] The escape behavior of bubbles was observed using an in-situ high-speed microscope camera. The distribution of bubbles ( Figure 8 and Fig. 9 ) indirectly proves the hydrophobicity of the catalytic material obtained in Example 1, and the results show that the nanorod-like morphology is conducive to the escape of bubbles during HER and OER reactions.

[0049] FeP / CoNiP / NF was measured using a three-electrode system. The specific steps are as follows: The catalytic material obtained in Example 1 was clamped on a platinum electrode clamp as a working electrode, Hg / HgO was used as a reference electrode, and a carbon rod was used as a counter electrode. HER and OER tests were performed in a 1 mol KOH solution. The polarization curve tests were all performed at a scan rate of 2~5 mV / s, except that the scan range of HER was -0.95~-2 V, and the scan range of OER was 0.3~1.5 V. Figure 4 (Polarization curve of OER) and Figure 5 (HER polarization curve) shows that the material is 2 At a current density of 1000 mA cm, the overpotentials of OER and HER (the potential in the OER / HER diagram minus 1.23 V / 0 V) are 268 mV and 159 mV, respectively. -2 The overpotentials are 375 mV (OER) and 234 mV (HER) at current densities of 1.3 Å and 2.1 Å, respectively. Figure 6 and Figure 7 The excellent stability of FeP / CoNiP / NF was demonstrated at 10 mA / cm -2 (OER) and -10 mA / cm -2 (HER) remained stable for at least 100 h.

[0050] Fig.10 The SEM image of the product obtained in Example 1 after OER reaction is shown. Figure 1 After comparison, it can be seen that the nanorod-like structure has better stability and the structure does not collapse or change after the OER reaction.

[0051] Example 2 The difference between Example 2 and Example 1 is that in step 2), the cobalt source, the iron source, ammonium fluoride and urea are added in a molar ratio of 4:1:6:30.

[0052] The SEM image of the product obtained in Example 2 is as follows Fig.11 As shown, it shows a nanorod-like structure. The electrochemical test was carried out using the method of Example 1. Fig.12 (Polarization curve of OER) and Fig.13 (HER polarization curve) shows that the material is 2 At a current density of 1000 mA cm, the overpotentials for OER and HER are 266 mV and 188 mV, respectively.-2 The overpotentials are 412 mV (OER) and 272 mV (HER) at current densities of 1.3 Å and 2.1 Å.

[0053] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step 2), no iron source is added, and the molar ratio of the cobalt source, ammonium fluoride and urea is 5:6:30.

[0054] The SEM image of the product obtained in Comparative Example 1 is as follows Fig.14 As shown, it shows a composite structure of flakes and nanorods. The electrochemical test was carried out using the method of Example 1. Fig.15 (Polarization curve of OER) and Fig.16 (HER polarization curve) shows that the material is 2 At a current density of 1000 mA cm, the overpotentials for OER and HER are 351 mV and 162 mV, respectively. -2 The overpotentials at the current density of 502 mV (OER) and 287 mV (HER). It can be seen that the overpotential of the product obtained in Comparative Example 1 is smaller than that of the product obtained in Example 1, which is because the nanorod-like heterostructure has better hydrophilicity and gas repellency and OER / HER activity.

[0055] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in step 2), no cobalt source is added, and the molar ratio of the iron source, ammonium fluoride and urea is 1:6:30.

[0056] The SEM image of the product obtained in Comparative Example 2 is as follows Fig.17 As shown, it shows a micrometer-scale flake structure. The electrochemical test was carried out using the method of Example 1. Fig.18 (Polarization curve of OER) and Fig.19 (HER polarization curve) shows that the material is 2 At a current density of 1000 mA cm, the overpotentials for OER and HER are 279 mV and 171 mV, respectively. -2 The overpotentials are 460 mV (OER) and 319 mV (HER) at current densities of 1.3 Å and 2.5 Å.

[0057] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in step 2), the cobalt source, the iron source, ammonium fluoride and urea are added in a molar ratio of 2:1:6:30.

[0058] The SEM image of the product obtained in Comparative Example 3 is as follows Fig. 20 As shown, it shows a micrometer-scale flake structure. The electrochemical test was carried out using the method of Example 1. Fig.21 (Polarization curve of OER) and Fig. 22 (HER polarization curve) shows that the material is 2 At a current density of 2.3 Å, the overpotentials of OER and HER are 273 mV and 225 mV, respectively.

[0059] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in step 2), the cobalt source, the iron source, ammonium fluoride and urea are added in a molar ratio of 6:1:6:30.

[0060] The SEM image of the product obtained in Comparative Example 4 is as follows Fig.23 As shown, it shows a micrometer-scale flake structure. The electrochemical test was carried out using the method of Example 1. Fig.24 (Polarization curve of OER) and Fig.25 (HER polarization curve) shows that the material is 2 At a current density of 2.3 Å, the overpotentials of OER and HER are 284 mV and 190 mV, respectively.

[0061] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for industrial production of super-gas-repellent iron phosphide / cobalt nickel phosphide electrocatalytic material, characterized in that: Using nickel foam as a substrate, array-arranged iron phosphide / cobalt phosphide nickel in nanorod-like structure is in-situ grown on its surface; The industrial production method of iron phosphide / cobalt nickel phosphide electrocatalytic material mainly includes the following steps: Step 1: Clean the nickel foam Step 2: Preparation of ferric hydroxide / cobalt nickel hydroxide precursor A cobalt source, an iron source, ammonium fluoride and urea are added to deionized water in a molar ratio of (3-5):1:6:30, and stirred to obtain a solution A. The nickel foam cleaned in step 1 is placed in the solution A, and is bathed in a water bath at a temperature of 60-90° C. for several hours. After the reaction is completed, the nickel foam is cooled to room temperature, and the nickel foam is taken out, and is rinsed with deionized water and ethanol for several times, and finally vacuum dried to obtain a nickel foam with an iron hydroxide / cobalt hydroxide nickel precursor; Step 3: Heat treatment of nickel foam with ferric hydroxide / cobalt hydroxide nickel precursor The nickel foam with the iron hydroxide / cobalt hydroxide nickel precursor obtained in step 2 is placed in a tube furnace, and is heated to 350-450°C at a heating rate of 2-5°C / min under the protection of an inert atmosphere for heat treatment, and is kept at this temperature for 1-5 hours, and is taken out after cooling to obtain a heat-treated product; Step 4: Preparation of bifunctional heterostructured iron phosphide / cobalt nickel phosphide electrocatalytic material A phosphorus source is placed in the upwind section of the tubular furnace, and the heat-treated product obtained in step 3 is placed 1-5 cm away from the phosphorus source. It is heated to 350-450°C at a heating rate of 2-5°C / min in an inert atmosphere for CVD phosphorus source deposition. The mixture is kept warm for 1-5 hours, and taken out after cooling. Thus, an array of iron phosphide / cobalt phosphide nickel in a nanorod-like structure is in situ grown on the surface of the nickel foam.

2. A method for industrially producing super-gas-repellent iron phosphide / cobalt nickel phosphide electrocatalytic materials according to claim 1, characterized in that: In step 1, the nickel foam is ultrasonically treated in a 2-3 mol hydrochloric acid solution, an acetone solution and a deionized water solution for several minutes in sequence to remove impurities in the nickel foam, and then dried in a low-temperature vacuum environment.

3. A method for industrially producing super-gas-repellent iron phosphide / cobalt nickel phosphide electrocatalytic materials according to claim 1, characterized in that: The cobalt source is at least one of cobalt nitrate and cobalt chloride; the iron source is at least one of ferric nitrate and ferric chloride.

4. A method for industrially producing super-gas-repellent iron phosphide / cobalt nickel phosphide electrocatalytic materials according to claim 1, characterized in that: In step 2, the vacuum drying temperature is 60-90°C.

5. A method for industrially producing super-gas-repellent iron phosphide / cobalt nickel phosphide electrocatalytic materials according to claim 1, characterized in that: In step 3 or step 4, the inert atmosphere is any one of argon, nitrogen, and a hydrogen-argon mixture.

6. A method for industrial production of super-gas-repellent iron phosphide / cobalt nickel phosphide electrocatalytic material according to claim 1, characterized in that: The phosphorus source is any one of sodium hypophosphite and red phosphorus.